PENGARUH PENERAPAN MODEL COOPERATIVE LEARNING TIPE THINK TALK WRITE (TTW) TERHADAP PEMAHAMAN KONSEP PADA SISWA DALAM MATA PELAJARAN EKONOMI: Studi Eksperimen Pada Siswa Kelas X SMA Negeri 8 Bandung - Anggi Nuraini, - (2012)
The participants of the study were the tenth grade students of SMA Negeri 8 Bandung, which were then classified into experimental group (class X-3) and control group (class X-2). This study was a quasi experimental study with pre and post test design. The data collection techniques of the study were N-Gain test, homogenity test, and normality test. Furthermore, the data computation was conducted by using SPSS 14.0. The results of the study showed that the implementation of Think Talk Write (TTW) from the Cooperative Learning Model gave positive impacts toward students' conceptual comprehension of Economics. This was shown from the difference of students' conceptual comprehension in the experimental and control groups. Based on the statistical results, students in the experimental group exhibited an increase of 0,34 in average, while students from the control group exhibited an increase of 0,24 in average regarding their level of conceptual comprehension of Economics.